“Trabalho forçado”: contexto histórico-econômico global, sistemas internacionais de proteção aos direitos humanos e as repercussões internas das demandas contra o Brasil - Almeida, Lívia Lemos Falcão de (2014)
The “forced labor”, i.e. the labor supply which is not based on the free and full consent of the worker and it figures as the most serious form of exploitation of human labor. This kind of work is rooted in slavery, what is an aggravated form of forced labor, based on the ownership of the individual. Since the nineteenth century, slavery was formally abolished in almost all States. During the twentieth century came into a type of “forced labor” similar to the slavery, although not based on the notion of ownership, have in common that the imposition of forced labor regimes, either through direct physical coercion; through psychological constraint; through induced debt, deception, withholding or confinement; or even by means (direct or indirect) that removing the dignity of the worker, the conditions for this type of labor. Such similar practices were (and are) applicants in Brazil. Internationally, many legal texts concern the prohibition of all forms of forced labor. It stands out, especially the Convention n. 29/1930 and n. 105/1957 of the International Labour Organisation (ILO), as well as international human rights treaties, global framework (such as the International Covenant on Civil and Political Rights, 1966) and American regional (such as the American Convention on Rights human, 1969). To guarantee compliance with international conventions, control mechanisms and safeguards were established. This present work will be featured applicable to the protection of freedom of labor in Brazil mechanisms. And among these, the so-called "ex post facto” mechanisms, from an analysis of two major international demands against Brazil in the field of “forced labor” will be shown – the first in the ILO and the second before the Inter-American Commission Human rights. Finally, will be examined the domestic repercussions of these international procedures, the executive levels, legislative and judicial.